Sticky Prices in the United States - Rotemberg, Julio J. (Journal of Political Economy, 1982)
It has often been argued that prices are sticky in the United States. However, the empirical papers that have claimed to support this view have not reflected any formal behavioral theory. This paper presents a theory that justifies price stickiness, namely, that firms, fearing to upset their customers, attribute a cost to price changes. The rational expectations equilibrium of an economy with many such firms is presented, estimated with postwar U.S. data, and tested against alternative hypotheses. The results largely support the model. Furthermore, the hypothesis that prices are not sticky is rejected by U.S. data.